Analysis of the Socialization of Anti-Corruption Values as an Effort to Build an Honest Generation from an Early Age for 6th Grade Students - Desty Endrawati Subroto; Deri Ardiari Kusumah; Siti Muniroh; Irba Virly Kalila Hidayat; Zia’ul Fatwa Andini Yusuf (Edujavare Publishing, 2025)
Corruption is a major problem hindering national progress and is often rooted in the weak installation of honest values from an early age. Therefore, anti-corruption education needs to be provided from elementary school as part of character building. This study aims to analyze the implementation of anti-corruption values socialization as an effort to build an honest generation from an early age among sixth-grade students of Ciwedus Elementary School, Bendung Village. The method used is a descriptive qualitative approach. The research subjects involved 45 male and female students participating in the Student Work Lecture (KKM) Group 05 of Bina Bangsa University. The instruments used were a pre-test and post-test consisting of 10 multiple-choice questions, adjusted to the level of understanding of elementary school students. The results showed that some students understood the meaning of honesty and could recognize behaviors that violate it. After the socialization, the post-test results showed a significant increase in students' understanding of the value of honesty and unlawful behavior. Observations also recorded students' enthusiasm and active involvement during the activity. In conclusion, this socialization was effective in instilling anti-corruption values from an early age, and the initial test plays an important role as a diagnostic tool in developing appropriate learning strategies.